Towards a Pluriversal Europe? The Performance Dispak Dispac'h – Crépuscule européen from Patricia Allio and Her Co-Creators as a Shift from the Universalist Monologue to Pluriversalist Dialogues - HECHT-AUSSENAC, Sylvan (Studia Universitatis Babeș-Bolyai Philosophia, 2026)
This article dreams and thinks the hypothesis of a utopian “pluriversal Europe” thanks to the study of the “agora-performance” Dispak Dispac’h – Crépuscule européen from Patricia Allio and her friends, colleagues and comrades. To explore Dispak Dispac’h – European Twilight’s pluriversalist aesthetics and politics, the paper investigates two directions. First, it outlines the concepts of “Pluriverse” and “pluriversalism” as a theoretical framework, examining the “ontological turn” in philosophy and anthropology, its political implications, and – briefly – some critiques of this current. In a second part, the aesthetics of the “agora-work of art” Dispak Dispac’h – European Twilight is analysed as an antidote to “monological universalism”, enabling to sketch out pluriversalist dialogues, and Dispak Dispac’h – European Twilight’s “artivist” approach is established as a way of overcoming the modern dualisms between art and life and between artworks and social struggles – even beyond the limits of twentieth-century documentary theatre –, and contributing to the emergence of a new, “pluriversal” Europe[1]. [1] This text was originally written in French thanks to Patricia Allio, who invited me to present it during the workshop « Faire agora : autour de Dispak, Dispac’h » organised by Prof. Dr. Sophie Lucet at the Université Rennes 2 on April 10th, 2024 (unpublished). Thanks to the invitation of PD Dr. Niels Weidtmann and Lect. Dr. Alina Noveanu, I then rewrote the paper and translated it into English thanks to DeepL to present it at the conference Europe – between Idea, Imagination and Reality. New Philosophical Perspectives at the Babeș-Bolyai University of Cluj on June 24th, 2025. The present text is the new corrected and rewritten version of the translation-adaptation. I would like to deeply thank Patricia Allio, Sophie Lucet, Niels Weidtmann and Alina Noveanu for their great support during this whole artistic, epistemological, ethical and political process.